Effect of yellow rice wine on anti-aging ability in aged mice induced by d-galactose - Rong Liu; Zukang Fu; Fengjie Zhang; Qingzhong Mao; Chunguang Luan; Xinglin Han; Jie Xue; Deliang Wang; Si Qin; Feike Hao (Food Science and Human Wellness)
The present study is focused on investigation of the health protective effect of yellow rice wine (YRW) in mice and the potential underlying mechanism. Symptoms of aging were induced in mice by using D-galactose (D-gal), and different doses of YRW (4, 8, and 12 mL/kg BW) were orally administrated to D-gal-treated mice for a period of six weeks. The in vivo data obtained in the present study preliminary indicated that YRW markedly increased the activity of antioxidant enzymes and reduced the concentration of MDA both in the brain and liver. Furthermore, a forced swim test showed that moderate intake of YRW (8 mL/kg BW) significantly decreased the duration of immobility, reduced the blood content of urea nitrogen and lactic acid, and increased hepatic glycogen storage. Besides, results from the Morris water maze test suggested that YRW significantly reversed cognitive impairment and also alleviated neuroapoptosis in the experimental mice by regulating the gene expressions of Bax/Bcl-2 and caspase-3. The above results indicated YRW has a potential anti-aging effect in mice and provided us certain molecular evidence for this action.